The everyday lives of sovereignty : political imagination beyond the state - Bryant, Rebecca (Professor of anthropology); Reeves, Madeleine (Cornell scholarship online., 2021)
"This book addresses popular assertions of sovereignty and projects of sovereign agency with particular reference to areas of disputed territory in contemporary Europe, Asia, North Africa and the Middle East"--